The Internet and its impact - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Back in 1999, the International Development Research Centre (IDRC) helped launch a competition for research projects on the social impact of communication and information technologies (ICTs) in Latin America and the Caribbean.